Duration and convexity of bonds - Čerović, Slobodan; Pepić, Marina; Čerović, Stanislav; Čerović, Nevena (The European Journal of Applied Economics, 2014)
The wide impact that interest rate changes have on business performance, the fact that all market participants are, more or less, exposed to interest rate risk, as well as high volatility in interest rates in recent years, make interest rate risk one of the most significant risks. It is impossible to neutralize interest rate risk completely, but it is desirable to reduce it to a minimum. In order to effectively manage it, interest rate risk must first be identified and measured. This paper aims to show the two methods of measuring the interest rate risk - duration and convexity.The concept of duration is a good indicator of changes in the price of bonds but only for small changes in the interest rates. In case of major changes, the duration gives overestimated/underestimated approximation of the bond price, because bond price-yield relationship is not linear. Therefore, when measuring interest rate risk, convexity of bonds must be taken into account. Modified duration and convexity taken together provide the best approximation of the sensitivity of bond prices to changes in interest rates.